Falsafah Pengajaran dan Pembelajaran Dalam Islam: Suatu Analisis Karya al-Zarnuji - Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2002)
The problem of teaching and learning is a fundamental issue in human and nation development. Man without knowledge is valueless and knowledge without a clear concept in it's teaching and learning is impasse and fruitless. Therefore, a generic, accurate and contemporary explanation of the concept is needed in order to establish a right force and field for the development of knowledge. This paper attempts to elaborate an Islamic tradition and concept of teaching and learning as an alternative in solving the related problems. This basically will be based on an analysis of al-Zarnuji's Ta'lim al-Muta'allim Tariq al-Ta'allum where the current challenges facing the teachers and students are reconsidered. In general, the scope of this paper is focused on an exposition and re-evaluation of the Islamic concept of teaching and learning, especially as demonstrated by al-Zarnuji. It is hoped that it will propose a comprehensive interpretation on issues related to place and reality of knowledge, as important criteria in choosing knowledge and teachers, the importance of mental and spiritual preparation in the process of teaching and learning, and some basic techniques in acquiring knowledge.